Significance of combined analysis of autoantibodies in diagnosis of primary biliary cirrhosis - CAO Changchun (Linchuang Gandanbing Zazhi, 2015)
ObjectiveTo evaluate the significance of combined analysis of different autoantibodies in the diagnosis of primary biliary cirrhosis (PBC). MethodsTwo-hundred and forty-five patients with liver diseases were randomly selected. According to the disease type, patients were divided into PBC group (n=162), autoimmune hepatitis (AIH) group (n=42), and liver disease control (LDC) group (n=41). ELISA assay was used to detect serum anti-mitochondrial antibody (AMA-M2) and antibodies against SP100 and GP210. Western blot assay was employed to detect serum anti-SLA antibodies. Indirect immunofluorescence assay was performed to detect serum AMA. Comparison of antibody positive rates between groups was carried out using the chi-square test and Fisher′s test. ResultsSerum AMA, AMA-M2, and anti-GP210 positive rates of the PBC group were 93.21%, 87.65%, and 19.75%, respectively, significantly higher than those of the AIH group, i.e., 19.05%, 7.14%, and 9.52%, respectively (χ2=97.311, P=0.001; χ2=98264, P=0001; χ2=10.312, P=0.012). The AMA, AMA-M2, and anti-GP210 positive rates of the PBC group were also significantly higher than those of the LDC group, i.e., 9.76%, 2.44%, and 7.32%, respectively (χ2=142.745, P=0.003; χ2=112.574, P=0.002; χ2=15.217, P=0.042). ConclusionSerum AMA has a remarkable meaning to PBC diagnosis, anti-SP100 gives a hint of PBC progression, and anti-GP210 plays a role in the diagnosis of AMA-negative PBC.